Analisisis Risiko Bahaya Keselamatan Dan Kesehatan Kerja Dengan Menggunakan Metode Hirarc Dan Fmea Pada Proses Finishing - Dwi Kurniawan; Widya Setiafindari (Jurnal Rekayasa Proses dan Industri Terapan, 2024)
PT Asian Isuzu Casting Center (AICC) is a company engaged in the Casting manufacturing industry. Work accidents at PT Asian Isuzu Casting Center (AICC) in 2021 to 2022 there are 8 cases of work accidents, namely the occurrence of hand injuries caught between the roller and the product on the finishing machine line A in August 2022, while in July 2022 in the processing section production of shotblast 2, with a wound The ring finger of the victim's right hand was caught in a pendulum plate which came off while helping with repair maintenance with the victim being lightly injured. In this study, the Hirarc method was used to identify an accident risk that could occur, and the Fmea method was used to analyze a system or material failure and evaluate the effects of the failure. The results of hazard identification show 7 potential hazards that have been identified. At every finishing post. for the Fmea method there are 4 potential hazards at each finishing post. From the results of observations and observations in the field carrying out repair controls such as installing signs on each production line so that the data can serve as a reminder when the operator is working, such as providing special lines for forklift operations (administrative control), safety controls for employees and safety helmets to minimize falling products (PPE), and control of the use of gloves, Provision of APAR in the work area.